Membrane Binding of α-Synuclein Stimulates Expansion of SNARE-Dependent Fusion Pore - Khounlo, Ryan; Hawk, Brenden J. D.; Khu, Tung-Mei; Yoo, Gyeongji; Lee, Nam Ki; Pierson, Josh; Shin, Yeon-Kyun (Frontiers in Cell and Developmental Biology, 2021)
SNARE-dependent membrane fusion is essential for neurotransmitter release at the synapse. Recently, α-synuclein has emerged as an important regulator for membrane fusion. Misfolded α-synuclein oligomers are potent fusion inhibitors. However, the function of normal α-synuclein has been elusive. Here, we use the single vesicle-to-supported bilayer fusion assay to dissect the role of α-synuclein in membrane fusion. The assay employs 10 kD Rhodamine B-dextran as the content probe that can detect fusion pores larger than ∼6 nm. We find that the SNARE complex alone is inefficient at dilating fusion pores. However, α-synuclein dramatically increases the probability as well as the duration of large pores. When the SNARE-interacting C-terminal region of α-synuclein was truncated, the mutant behaves the same as the wild-type. However, the double proline mutants compromising membrane-binding show significantly reduced effects on fusion pore expansion. Thus, our results suggest that α-synuclein stimulates fusion pore expansion specifically through its membrane binding.